Individual prognosis of abutment teeth - Laura Sofía Osorio-Vélez (Universidad de Antioquia, 2015)
Establishing accurate prognosis after correct diagnosis is the most important point of reference in our clinical practice. The need to correctly predicting teeth permanence in the mouth has prompted each dental discipline to find ways to establish it. Since prosthodontics, or oral rehabilitation, incorporates the procedures of other disciplines and usually is the one that finishes most treatments, it should review all the factors affecting the prognosis of comprehensive treatment. Below is a review of dental and periodontal considerations for prognosis in prosthodontics, as well as the implications of treatments performed on abutment teeth in order to retain them, and the strategic weight of each abutment.